Hereditary Spastic Paraplegia and Future Therapeutic Directions: Beneficial Effects of Small Compounds Acting on Cellular Stress - Gumeni, Sentiljana; Vantaggiato, Chiara; Montopoli, Monica; Orso, Genny (Frontiers in Neuroscience, 2021)
Hereditary spastic paraplegia (HSP) is a group of inherited neurodegenerative conditions that share a characteristic feature of degeneration of the longest axons within the corticospinal tract, which leads to progressive spasticity and weakness of the lower limbs. Mutations of over 70 genes produce defects in various biological pathways: axonal transport, lipid metabolism, endoplasmic reticulum (ER) shaping, mitochondrial function, and endosomal trafficking. HSPs suffer from an adequate therapeutic plan. Currently the treatments foreseen for patients affected by this pathology are physiotherapy, to maintain the outgoing tone, and muscle relaxant therapies for spasticity. Very few clinical studies have been conducted, and it’s urgent to implement preclinical animal studies devoted to pharmacological test and screening, to expand the rose of compounds potentially attractive for clinical trials. Small animal models, such as Drosophila melanogaster and zebrafish, have been generated, analyzed, and used as preclinical model for screening of compounds and their effects. In this work, we briefly described the role of HSP-linked proteins in the organization of ER endomembrane system and in the regulation of ER homeostasis and stress as a common pathological mechanism for these HSP forms. We then focused our attention on the pharmacodynamic and pharmacokinetic features of some recently identified molecules with antioxidant property, such as salubrinal, guanabenz, N-acetyl cysteine, methylene blue, rapamycin, and naringenin, and on their potential use in future clinical studies. Expanding the models and the pharmacological screening for HSP disease is necessary to give an opportunity to patients and clinicians to test new molecules.